Neuronal activation in patients with mild and moderate traumatic brain injury during working memory tasks - Fitzrol, Diana Noma (2020)
Background and Objective Cognitive impairment in patients following TBI is a significant cause of morbidity both to patients and their families. Memory impairment is one of the most common complaint patients and their families have as it impairs patients’ daily function. Current neuroimaging modalities allows us to study the neuronal activation relevant to working memory in patients. Methods Patients who sustained mTBI/ modTBI, between the age of 18 to 65 years old and managed in Hospital Universiti Sains Malaysia were recruited into the study. These patients and a control group underwent fMRI scanning where they concurrently performed n-back tasks of 4 different memory loads. These fMRI scans were performed at 6 to 10 weeks postinjury and at 6 months post-injury. These cohort of subjects also had neuropsychology assessments performed at the same two time period as the fMRI. Results